Novel 'heavy' dyes for retinal membrane staining during macular surgery: multicenter clinical assessment. (20th June 2013) - Veckeneer, Marc; Mohr, Andreas; Alharthi, Essam; Azad, Rajvardhan; Bashshur, Ziad F.; Bertelli, Enrico; Bejjani, Riad A.; Bouassida, Brahim; Bourla, Dan; Crespo, Iñigo Corcóstegui; Fahed, Charbel; Fayyad, Faisal; et al.
Abstract. Purpose: To evaluate the feasibility of two novel 'heavy' dye solutions for staining the internal limiting membrane (ILM) and epiretinal membranes (ERMs), without the need for a prior fluid‐air exchange, during macular surgery. Methods: In this prospective nonrandomized multicenter cohort study, the high molecular weight dyes ILM‐Blue™ [0.025% brilliant blue G, 4% polyethylene glycol (PEG)] and MembraneBlue‐Dual™ (0.15% trypan blue, 0.025% brilliant blue G, 4% PEG) were randomly used in vitrectomy surgeries for macular disease in 127 eyes of 127 patients. Dye enhanced membrane visualization of the ILM and ERMs, 'ease of membrane peeling', visually detectable perioperative retinal damage, postoperative best‐corrected visual acuity (BCVA), dye remnants and other unexpected clinical events were documented by 21 surgeons. Results: All surgeries were uneventful, and a clear bluish staining, facilitating the identification, delineation and removal of the ILM and ERMs, was reported in all but five cases. None of the surgeries required a fluid‐air exchange to assist the dye application. BCVA at 1 month after surgery improved in 83% of the eyes in the MembraneBlue‐Dual™ group and in 88% in the ILM‐Blue™ group. No dye remnants were detected by ophthalmoscopy, and no retinal adverse effects related to the surgery or use of the dyes were observed. Conclusion: The 'heavy' dye solutions ILM‐Blue™ and MembraneBlue‐Dual™ can be injected into a fluid‐filled vitreous cavity and may facilitate staining and removal of the ILM and/or ERMs in macular surgery without an additional fluid‐air exchange.